2014
DOI: 10.1137/130924172
|View full text |Cite
|
Sign up to set email alerts
|

Upper Bound Constructions for Untangling Planar Geometric Graphs

Abstract: For every n ∈ N, we construct an n-vertex planar graph G = (V, E) and n distinct points p(v), v ∈ V , in the plane such that in any crossing-free straight-line drawing of G, at most O(n .4948 ) vertices v ∈ V are embedded at points p(v). This improves on an earlier bound of O( √ n) by Goaoc et al. [Discrete Comput. Geom., 42 (2009), pp. 542-569].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The goal is to do so while keeping fixed (i.e., not changing the location of) as many vertices as possible. Several papers have studied the untangling problem [18,4,7,3,11,15,20]. It is known that general n-vertex planar graphs can be untangled while keeping Ω(n 0.25 ) vertices fixed [3] and that there are n-vertex planar graphs that cannot be untangled while keeping Ω(n 0.4948 ) vertices fixed [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal is to do so while keeping fixed (i.e., not changing the location of) as many vertices as possible. Several papers have studied the untangling problem [18,4,7,3,11,15,20]. It is known that general n-vertex planar graphs can be untangled while keeping Ω(n 0.25 ) vertices fixed [3] and that there are n-vertex planar graphs that cannot be untangled while keeping Ω(n 0.4948 ) vertices fixed [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have studied the untangling problem [18,4,7,3,11,15,20]. It is known that general n-vertex planar graphs can be untangled while keeping Ω(n 0.25 ) vertices fixed [3] and that there are n-vertex planar graphs that cannot be untangled while keeping Ω(n 0.4948 ) vertices fixed [4]. Asymptotically tight bounds are known for paths [7], trees [11], outerplanar graphs [11], and planar graphs of treewidth two [20].…”
Section: Introductionmentioning
confidence: 99%
“…This has almost been matched by an Ω(n 2/3 ) lower bound by Cibulka [8]. Several papers have studied the untangling problem [5,6,8,15,17,21,22]. Asymptotically tight bounds are known for paths [8], trees [15], outerplanar graphs [15], and planar graphs of treewidth two and three [9,22].…”
Section: Applications and Related Workmentioning
confidence: 96%
“…For general planar graphs there is still a large gap. Namely, it is known that every planar graph can be untangled while keeping Ω(n 0.25 ) vertices fixed [5] (this answered a question by Pach and Tardos [21]) and that there are planar graphs that cannot be untangled while keeping Ω(n 0.4948 ) vertices fixed [6]. Theorem 1 can help close this gap, whenever a good bound on collinear sets is known.…”
Section: Applications and Related Workmentioning
confidence: 99%
“…Since we can simply take any plane embedding of G 1 , use the same embedding for G 2 and then untangle G 2 , it immediately follows that every two planar graphs on n vertices admit a 4 (n + 1)/2-PSGE. In the other direction, Cano et al [7] showed the existence of a graph and a straight-line drawing of this graph such that in any planar untangling, the embedding of all but O(n .4965 ) vertices has to change. However, an upper bound for untangling does not have direct implications for PSGE because untangling is more restrictive compared to PSGE: In the untangling problem the positions of all vertices, in particular, of those that remain fixed, are given, whereas in PSGE one may select suitable positions for those vertices.…”
Section: Introductionmentioning
confidence: 99%